2009
DOI: 10.1136/jnnp.2009.179069
|View full text |Cite
|
Sign up to set email alerts
|

Physiological identification of the human pedunculopontine nucleus

Abstract: Background The pedunculopontine nucleus (PPN) is a brainstem structure with widespread connections to the basal ganglia. Despite the recent introduction of PPN deep brain stimulation (DBS) for the treatment of gait disorders, little is known about its physiology in humans. Methods We analyzed the discharge characteristics of single neurons in the PPN region in four patients and PPN local field potentials (LFP) in one patient, recorded during the course of DBS implantation. Two patients had Parkinson’s diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 28 publications
5
40
1
Order By: Relevance
“…In some patients, PPN DBS reduces gait and freezing problems unresponsive to drug and conventional stimulation approaches directed at subthalamic and pallidal targets, reduces falls and occasionally improves patients' state of vigilance and quality of sleep (Pereira et al, 2008;Ferraye et al, 2010). The magnitude of the effects, the exact location of the stimulation electrode and best technique of implantation of DBS leads into this nucleus are still being debated (Aravamuthan et al, 2007(Aravamuthan et al, , 2008(Aravamuthan et al, , 2009Weinberger et al, 2008;Fu et al, 2009;Shimamoto et al, 2010). There have also been several small experimental trials of extradural motor cortex stimulation in human patients (Benvenuti et al, 2006;Strafella et al, 2007;Cilia et al, 2007Cilia et al, , 2008Arle et al, 2008;Lefaucheur, 2009;Pagni et al, 2008).…”
Section: New Targets For Dbs In Pdmentioning
confidence: 99%
“…In some patients, PPN DBS reduces gait and freezing problems unresponsive to drug and conventional stimulation approaches directed at subthalamic and pallidal targets, reduces falls and occasionally improves patients' state of vigilance and quality of sleep (Pereira et al, 2008;Ferraye et al, 2010). The magnitude of the effects, the exact location of the stimulation electrode and best technique of implantation of DBS leads into this nucleus are still being debated (Aravamuthan et al, 2007(Aravamuthan et al, , 2008(Aravamuthan et al, , 2009Weinberger et al, 2008;Fu et al, 2009;Shimamoto et al, 2010). There have also been several small experimental trials of extradural motor cortex stimulation in human patients (Benvenuti et al, 2006;Strafella et al, 2007;Cilia et al, 2007Cilia et al, , 2008Arle et al, 2008;Lefaucheur, 2009;Pagni et al, 2008).…”
Section: New Targets For Dbs In Pdmentioning
confidence: 99%
“…San Francisco, USA [33]. This group targeted the PPN based on MRI at a point superolateral to the decussation of the superior cerebellar peduncles on T2-weighted fast spin echo images.…”
Section: Stereotactic Targetingmentioning
confidence: 99%
“…Shimamoto et al [29] found that PPN neurons had significantly more burst discharges compared with the neurons from the region dorsal to the PPN. Weinberger et al [30] also observed more ‘bursty' cells within the PPN than those neurons found superiorly or inferiorly to the PPN.…”
Section: Discussionmentioning
confidence: 99%